Semantyka przymiotnika "piękny" a znaczenie innych leksemów wyrażających ocenę estetyczną = Semantics of the adjective "piękny" ("beautiful") vs the meaning of other lexemes expressing aesthetic assessment - Szymańska, Monika (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper presents a comparison between semantic properties of the adjective "piękny" ("beautiful") and properties of other adjectives expressing aesthetic assessment, including those whose meaning, apart from the element of aesthetic assessment, contains additional components that provide the characteristics of the object defined by the adjective.
Keywords: przymiotnik ?piękny?; wartościowanie w języku; analiza korpusowa; adjective ?piękny? (?beautiful?); valuation in language; corpus analysis